HAMKA's Thoughts on Educational Philosophy Based on Prophetic Islamic Values - Nur Khosiah; Moh Nurhakim; Syaiful Amin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Educators are agents of change who are responsible for meeting the needs of students by seeking the various potentials possessed by students. be it cognitive, affective or psychomotor in accordance with the values ​​of Islamic teachings. Educators occupy their role as one of intellectual formation, morals, and devotion to the Holy Kholik SWT. The research aims to find out HAMKA's thoughts about educational philosophy based on prophetic values. The method in this research uses library research (Library Research). This research uses two types of data sources: primary and secondary. The primary data will use a study of the concept of HAMKA thinking. And the secondary data is from various research journals and books regarding educational philosophy based on prophetic values ​​which are summarized and collected to strengthen theory, a reference for this research. HAMKA's thoughts on educational philosophy based on prophetic values ​​include: Integrating science and morals, humanitarian orientation, critical of secular thinking, the importance of character education.